Kemampuan Menyimak Bahasa Jerman Melalui Media Video Easy German - Yusnita Yusnita; Laelah Azizah; Jufri Jufri (Universitas Negeri Makassar, 2022)
Abstract. This study aims to improve the ability to listen to German language for class XI Mipa 5 students of SMA Kartika XX-1 Makassar through Easy German video media. This research is a class action research consisting of two cycles, each cycle consisting of the stages of planning, implementation, observation and reflection. The subjects of the study were students of class XI Mipa 5, totaling 25 people. The data of this study consists of qualitative and quantitative data. Qualitative data obtained from the data from the observations of teachers and students. Qualitative data were obtained through tests of the ability to listen to German in cycles I and II. The value of the ability to listen to students in the first cycle was obtained on average 79.81 and in cycle II the average score obtained by students was 91.2. This shows that the use of Easy German video media can improve the ability to listen to German language for class XI mipa sma Kartika Makassar students.Keywords: Listening, Easy German Video, Upgrade.